Culture and phenotype of canine valvular interstitial cells - Heaney, Allison Mahoney (Kansas State University, 2007)
Degenerative valve disease is the most common cardiac affliction facing our canine population. To date, canine research has focused on characterizing the disease itself and the histopathological features. Because of the ability to routinely repair or replace diseased valves in human medicine, research focus in humans has been on perfecting these techniques rather than elucidating etiology. The recent interest in valvular interstitial cells has been primarily due to their capacity to degrade collagen with the knowledge that disorganized collagen is a hallmark characteristic of degenerative valve disease. In this project, an easily reproducible cell culture protocol for canine valvular interstitial cells was developed. These cells were phenotyped by utilization of RT-PCR and immunocytochemistry. The use of these cells in a research project looking at response to endothelin exposure with and without protection of vitamin E is demonstrated as an example of the unlimited possibilities for these cells to elucidate not only the etiology of the disease process but also the response to therapy.
Keywords: Canine; Valve; Valvular Interstitial Cells; Mitral Valve Prolapse; Myxomatous Degeneration; Degenerative Valve Disease; Biology, Veterinary Science (0778)